KEABSAHAN PERJANJIAN PINJAM NAMA ANTARA WARGA NEGARA ASING TERHADAP WARGA NEGARA INDONESIA - Oriza Imanda Pratama Ismi Putri; Fatma Ulfatun Najicha (LPPM Universitas Ekasakti Padang, 2021)
This study aims to analyze the legal provisions in the regulations regarding the nominee agreement and the form of sanctions given to the notary making the nominee agreement deed that is contrary to the UUPA. This type of research is normative juridical and the approach method used is the statutory approach. The results of this study are that the nominee agreement between foreign citizen and Indonesian citizen does not meet the objective requirements for the validity of the agreement, because it does not contain a lawful cause. This is because this agreement was made to do things that are prohibited by law. Foreign nationals do not have ownership rights to land in Indonesia, but only have usufructuary rights to land. This has been regulated in Article 42 of the UUPA. In relation to the notary making the deed of the nominee agreement which is contrary to the UUPA, then administratively, the notary has violated article 16 paragraph (1) letter d of the UUJN, so that it can be subject to sanctions in the form of verbal warning, written warning, temporary dismissal, respectful dismissal, or dishonorable dismissal.